1997
DOI: 10.1074/jbc.272.46.29317
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of Group VI Ca2+-independent Phospholipase A2 Blocks Phospholipid Fatty Acid Remodeling in Murine P388D1 Macrophages

Abstract: A major issue in lipid signaling relates to the role of particular phospholipase A 2 isoforms in mediating receptor-triggered responses. This has been difficult to study because of the lack of isoform-specific inhibitors. Based on the use of the Group VI Ca 2؉ -independent phospholipase A 2 (iPLA 2 ) inhibitor bromoenol lactone (BEL), we previously suggested a role for the iPLA 2 in mediating phospholipid fatty acid turnover (Balsinde, J., Bianco, I. D., Ackermann, E. J., Conde-Frieboes, K., and Dennis, E. A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
216
4
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(238 citation statements)
references
References 25 publications
(46 reference statements)
12
216
4
6
Order By: Relevance
“…21,22 Loss of PLA2G6A function leads to significant reductions in the amount of AA incorporated into the cell membrane. 23 …”
Section: Pla2s and Aamentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Loss of PLA2G6A function leads to significant reductions in the amount of AA incorporated into the cell membrane. 23 …”
Section: Pla2s and Aamentioning
confidence: 99%
“…[55][56][57] As loss of PLA2G6A function results in reduced cell membrane AA levels, variations in this gene may be responsible for these results. 23 PLA2s and in vivo phospholipid metabolism 31-Phosphorus magnetic resonance imaging ( 31 P MRS) allows measurement of membrane phospholipid dynamics in the living brain. 45 31 P MRS of drugnaïve first episode schizophrenia patients reveals significantly increased breakdown and reduced creation of cellular membranes in never treated patients with schizophrenia.…”
Section: Pla2s and Reduced Pufas In Schizophreniamentioning
confidence: 99%
“…Hence, inhibition of iPLA 2 results in reduced levels of lysophospholipid acceptors, which in turn leads to a decreased incorporation of AA into PLs under unstimulated conditions (14,(23)(24)(25). When the effect of zymosan on AA incorporation was assayed in monocytes treated with BEL, and hence exhibiting diminished lysophospholipid levels (44), the response was slightly but significantly reduced (Fig.…”
Section: Stimulated Incorporation Of Aa Into Pls Of Activated Cells Imentioning
confidence: 99%
“…Our previous work has indicated that iPLA 2 is a significant contributor to the steady-state lysophospholipid level in resting phagocytic cells (23)(24)(25)43). Hence, inhibition of iPLA 2 results in reduced levels of lysophospholipid acceptors, which in turn leads to a decreased incorporation of AA into PLs under unstimulated conditions (14,(23)(24)(25).…”
Section: Stimulated Incorporation Of Aa Into Pls Of Activated Cells Imentioning
confidence: 99%
See 1 more Smart Citation